Cartografía do despoboamento na Galicia oriental. Análise a escala parroquial - Moragón Arias, María Pilar; Pazo Labrador, Alberto José (Madrygal. Revista de Estudios Gallegos, 2010)
In this article we use the parish level to reveal the extent of depopulation in eastern Galicia. Mapping presented tendency to express that through analysis of various time periods since 1900, with regard to change in the occupation densities and demographic change on this scale.